The Trevo device: preclinical data of a novel stroke thrombectomy device in two different animal models of arterial thrombo-occlusive disease. (20th August 2011) - Nogueira, Raul G; Levy, Elad I; Gounis, Matthew; Siddiqui, Adnan H
Abstract : Background: The currently available mechanical devices fail to achieve recanalization in as many as 20–40% of proximal arterial occlusion strokes. Objective: The preclinical evaluation of the safety and efficacy of a novel thrombectomy device designed to achieve immediate flow restoration by quickly removing clot is reported. Methods: Four confirmatory animal studies were performed with the Trevo device (Concentric Medical Inc, Mountain View, California, USA) in the swine (n=2) and canine (n=1) models of arterial thrombo-occlusive disease employing autologous thrombin generated thrombi. The angiographic response and the degree of device–clot incorporation were evaluated. High resolution flat panel three-dimensional CT was performed to further define the in vivo device–thrombus–vessel interaction. Finally, samples of three swine vessels treated with six passes of the device were explanted for histopathological analysis. Results: A total of 16 clots of variable hardness and consistency were implanted in a variety of vascular settings, including the swine internal maxillary, lingual and forelimb arteries as well as the canine external carotid and vertebral arteries. Thrombolysis in Myocardial Infarction (TIMI) 2–3 reperfusion was achieved in all cases immediately after device deployment. All 16 clots were retrieved after one (n=15) or two (n=1) passes with the device. Histopathological analysis demonstrated severe disruption of the intima but no hemorrhage of media or adventitia. Conclusion: The experimental data suggest that the Trevo device is highly effective at achieving immediate reperfusion of occluded arteries without causing any clinically significant disruption of vascular integrity.